Implementation of Class Management in PAI Subjects in Class VIII SMPN 2 East Karawang - Salwa Fauziah; Abdurrohim, Abdurrohim; Taufik Mustofa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study investigates the implementation of classroom management in Islamic Education (PAI) teaching in Grade VIII at SMPN 2 East Karawang. The research is motivated by the importance of effective classroom management in creating a conducive learning environment. The aim is to understand the strategies, methods, media used, as well as the challenges involved in PAI classroom management and efforts made to address them. The research methodology employed is a qualitative approach involving observation, interviews, and documentation. Findings indicate that teachers employ various strategies such as utilizing visual and audio-visual media, and implementing interactive approaches to enhance student engagement. Identified obstacles include student fatigue and inadequate classroom lighting. The study concludes that good classroom management is crucial for enhancing learning effectiveness, and emphasizes the need for teachers to continuously develop their classroom management skills and strategies. The implications of these findings underscore the necessity for improving the physical conditions of classrooms and providing additional support for students to create a more optimal and supportive learning environment.